Corrosion inhibition of mild steel by cassava peel powder in hydrochloric acid medium - Ismail, Nor Khuza Hidayu; Sobri, Shafreeza; Haris, Nur Izzah Nabilah (Tamkang University Press, 2022)
Cassava peel powder (CPP) was utilized as a green corrosion inhibitor to reduce the mild steel (MS) corrosion rate (Rc) in acidic media. The weight-loss method was employed to investigate the Rc and inhibition efficiency (IE) of the mild steel specimen in uninhibited and inhibited 1.0 M HCl solution with CPP dosages of 0.2, 0.4, 0.6, 0.8 and 1.0 g for a set amount of immersion times ranging from 24 to 120 hours. Results show that the inhibitive performance of CPP increased as the inhibitor dosages increased from 0.2 to 1.0 g but decreased with a rise in immersion time, inferring that longer immersion time is unfavorable. CPP dosage of 1.0 g attained the highest inhibition efficiency of 86.77% after 24 hours immersion time. Optimization study via Response Surface Methodology (RSM) demonstrates that the optimum conditions are estimated at 1.0 g CPP dosage and 57 hours immersion period, with an efficiency of 87.20%. The thermodynamic analysis revealed that the inhibition process is spontaneous and obeyed Langmuir isotherm, and the mechanism of inhibition inclined towards chemisorption.